Becoming an emotional literacy support assistant (ELSA) : exploring the relationship between training, supervision and self-efficacy - Garwood, H. L. (University of Essex, 2012)
Despite rising use of the Emotional Literacy Support Assistant (EL SA) programme, and the modest body of research investigating its impact, little is known about the perspectives of school Support Assistants (SAs) receiving this training. The purpose of this mixed method study is to: a) address the impact of ELSA supervision on aspects of SAs' self-efficacy, and b) to explore how ELSA training and supervision is experienced by SAs taking up the role. Participants are the first cohort of SAs undertaking the ELSA programme in an outer London borough. Questionnaires were administered pre- and post-supervision to specifically investigate the impact of group s~ision on SAs' self-efficacy -1·-" (general and specific). 26 SAs completed both pre- and post-test questionnaires following four group supervision sessions. Findings broadly indicate that group supervision impacted positively on SAs' self-efficacy. Analysis of interviews with a sample of seven SAs using Grounded Theory revealed that, under certain conditions, participants were empowered through the mechanisms of the programme. Enhanced self-efficacy and self-reflection, and clarity of professional identity, were identified as central to the empowerment process. TIns study aims to contribute to a more complete understanding of how the ELSA programme enables SAs to take up their role effectively, and to gain a more nuanced understanding of the relationship between training, group supervision and self-efficacy. It forms part of a growing body of research on the training and professional development of SAs. The study further contributes to the evidence-base for the ELSA programme.